Alteration of archeological and natural analogs for radioactive waste glass under different environmental conditions - Marcial, Jose; Chesnutt, Julian; Neeway, James J.; Gichon, Eshchar; Thorpe, Clare L.; Zhu, Zihua; Golovchak, Roman; Cebulski, Jozef; Niedzielski, Przemyslaw; Szostek, Malgorzata; Luksic, Steven; Choi, Seungrag; et al. (Npj Materials degradation, 2025)
Approximately 200,000 m 3 of legacy radioactive waste from plutonium production stored at U.S. Department of Energy’s Hanford site will be immobilized in glass for disposal. The glass must limit radionuclide release into the environment for thousands of years, which is challenging to assess in laboratory experiments. Long-term alteration signatures on analog glasses can approximate how radioactive waste glass will perform over extended periods. Different glasses buried for tens to thousands of years at sites subject to variable climates and environments were selected for analysis. Surface altered layers that formed during glass corrosion were characterized. The thickness, chemistry, and morphology of surficial layers are discussed in terms of glass chemistry and burial conditions. Glass from arid environments, e.g., Timna (Israel), exhibited thinner surface layers (~2 µm) compared to glasses altered in humid conditions, e.g., Dobkowice (Poland: up to 59 µm), suggesting a role of burial environment and climate in long-term durability.